2020
DOI: 10.3390/en13061344
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Modeling of Fluid Flow and Heat Transfer in Petroleum Industries and Geothermal Applications

Abstract: This Special Issue of Energies is dedicated to all aspects of fluid flow and heat transfer in geothermal applications, including the ground heat exchanger, conduction, and convection in porous media [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Studies have shown that the thermal conduction process of thermal storage has an important impact on the development, extraction and recovery of energy in geothermal reservoirs. Therefore, it is of great significance to study the thermal characteristics of geothermal reservoir and extract heat reasonably and efficiently for geothermal mining engineering [1,2,3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the thermal conduction process of thermal storage has an important impact on the development, extraction and recovery of energy in geothermal reservoirs. Therefore, it is of great significance to study the thermal characteristics of geothermal reservoir and extract heat reasonably and efficiently for geothermal mining engineering [1,2,3,4].…”
Section: Introductionmentioning
confidence: 99%